Molecular characterization of the type 3 (MR/K) fimbriae of Klebsiella pneumoniae. - Gerlach, G F (1988)
The expression of type 3 (MR/K) fimbriae by Klebsiella pneumoniae requires the production of at least four polypeptides with molecular masses of 20.5, 25, 34, and 78 kilodaltons. The genes encoding these polypeptides are located on a gene cluster 5,500 base pairs in length. The nucleotide sequence of the major fimbrial structural gene was determined, and its transcription was shown to initiate in vitro 157 base pairs upstream of the translational start site. The predicted amino acid sequence for the fimbrial subunit comprised 202 residues, including a signal peptide of 22 amino acids. Despite similarities in the organization of the gene cluster, the nucleotide and the amino acid sequence of the major fimbrial subunit revealed little agreement with other known fimbrial subunit sequences.